A RURAL SCHOOL OF MUNICIPALITY CASTILHO AND FIELD OF EDUCATION - Sant'ana, Divanir Zaffani [UNESP]; Hespanhol, Rosangela Aparecida Medeiros [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2017)
This article aimed to verify if the implementation of the National Policy Field Education occurred in a school located in the rural area of Castilho-SP, EMEIEF Profa. Maria Dauria Silva Oliveira, from the analysis of the vision of the direction, the pedagogical coordination and the teachers, as well as to verify the students' perception about the teaching and the life that they take in the field. The methodology used included direct observation in school; the application of standardized questionnaires specific to each of the segments researched, and a semi-structured interview (recorded) with the school director; as well as consultations in data from secondary sources. It was verified that the school has good physical infrastructure; since 2015 it was registered as a field school and used specific textbook, but there was not, until 2016, the initiative by the municipal government to qualify the teachers' team and direction in relation to Rural Education. Although the Director has set up a vegetable garden and used it for some didactic activities, the teachers reported not knowing the proposal of it and, therefore, they do not use the contents and methodology recommended by the National Policy of Rural Education during the classes.
Keywords: School field; vision direction and teachers; teacher qualifications; educational policy